2022
DOI: 10.3390/jcdd9020063
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte-Mediated Cardiac Repair after Myocardial Infarction in Non-Regenerative vs. Regenerative Systems

Abstract: Innate and adaptive leukocytes rapidly mobilize to ischemic tissues after myocardial infarction in response to damage signals released from necrotic cells. Leukocytes play important roles in cardiac repair and regeneration such as inflammation initiation and resolution; the removal of dead cells and debris; the deposition of the extracellular matrix and granulation tissue; supporting angiogenesis and cardiomyocyte proliferation; and fibrotic scar generation and resolution. By organizing and comparing the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 242 publications
2
9
0
Order By: Relevance
“…Clofibrate administration was able to prevent these effects. It is well known that neutrophils and/or macrophages show a strong affiliation to invade the damaged area due to the apoptotic cardiomyocytes and the need for their removal; however, in the present paper, we did not evaluate the cell subpopulations infiltrated [ 6 , 30 ]. Our data are in line with several studies that have demonstrated that MetS signs, such as obesity, insulin resistance, lipotoxicity, and inflammation, play an important role in myocardial fibrosis by activating several downstream signaling cascades [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clofibrate administration was able to prevent these effects. It is well known that neutrophils and/or macrophages show a strong affiliation to invade the damaged area due to the apoptotic cardiomyocytes and the need for their removal; however, in the present paper, we did not evaluate the cell subpopulations infiltrated [ 6 , 30 ]. Our data are in line with several studies that have demonstrated that MetS signs, such as obesity, insulin resistance, lipotoxicity, and inflammation, play an important role in myocardial fibrosis by activating several downstream signaling cascades [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines and other growth factors recruit immune cells into the infarcted region in the damaged myocardium, which intensifies the inflammatory reaction and modulates downstream signaling cascades involved in remodeling and reparative responses [ 30 ]. Moreover, an imbalance in the equilibrium of synthesis and degradation of extracellular matrix components occurs after I/R injury; hence, we decided to evaluate the levels of fibrosis and the expression of MMP-2 in our model.…”
Section: Discussionmentioning
confidence: 99%
“…3a). These 2 time points represent acute inflammation (1 dpci) and regenerative stages (7 dpci), respectively 15 . A total of 70,783 cells from 2 replicates of 4 organs and 3 treatment groups (uninjured or Ctrl, 1 dpci, and 7 dpci) passed quality control filters and were included in the analyses (Fig.…”
Section: Cardiac and Systemic Responses After Heart Injury In Zebrafishmentioning
confidence: 99%
“…; https://doi.org/10.1101/2023.03. 15.532865 doi: bioRxiv preprint govern successful myocardial regeneration. Swift neutrophil infiltration to the injury site in the acute inflammation stage (within 1 day of injury) is followed by macrophage recruitment that spans the inflammatory and regenerative stages (until 7 days after injury), while NK or T cells take on activity during the regeneration stage 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Once inside the ischemic area, monocytes give rise to macrophages, which remove the cellular debris and extracellular matrix. The number of pro-inflammatory macrophages inside the infarcted heart peaks between day 3 and 4 [ 30 , 31 , 32 ]. The inflammatory phase, which lasts around 4 days, is the first of three stages that characterize cardiac injury and repair secondary to MI, and it is followed by the regenerative and the maturation phases [ 33 , 34 ] ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%